Effect of Wholegrain Flour Particle Size in Bread on Glycaemic and Insulinaemic Response among People with Risk Factors for Type 2 Diabetes: A Randomised Crossover Trial - Mete E; Haszard J; Perry T; Oey I; Mann J; Te Morenga L (MDPI (Basel, Switzerland), 2021)
Wholegrain flour produced by roller-milling is predominantly comprised of fine particles, while stoneground flour tends to have a comparatively smaller proportion of fine particles. Differences in flour particle size distribution can affect postprandial glycaemia in people with type 2 diabetes and postprandial insulinaemia in people with and without type 2 diabetes. No prior studies have investigated the effect of wholegrain flour particle size distribution on glycaemic or insulinaemic response among people with impaired glucose tolerance or risk factors for type 2 diabetes. In a randomised crossover study, we tested the 180-min acute glycaemic and insulinaemic responses to three wholegrain breads differing in flour particle size and milling method: (1) fine roller-milled flour, (2) fine stoneground flour, and (3) coarse stoneground flour. Participants (n = 23) were males and females with risk factors for type 2 diabetes (age 55-75 y, BMI >28 kg/m2, completing less than 150 min moderate to vigorous intensity activity per week). Each test meal provided 50 g available carbohydrate, and test foods were matched for energy and macronutrients. There was no significant difference in blood glucose iAUC (incremental area under the curve) between the coarse stoneground flour bread and the fine stoneground flour bread (mean difference -20.8 (95% CI: -51.5, 10.0) mmol·min/L) and between the coarse stoneground flour bread and the fine roller-milled flour bread (mean difference -23.3 (95% CI: -57.6, 11.0) mmol·min/L). The mean difference in insulin iAUC for fine stoneground flour bread compared with the fine roller-milled flour bread was -6.9% (95% CI: -20.5%, 9.2%) and compared with the coarse stoneground flour bread was 9.9% (95% CI: -2.6%, 23.9%). There was no evidence of an effect of flour particle size on postprandial glycaemia and insulinaemia among older people with risk factors for type 2 diabetes, most of whom were normoglycaemic.
Keywords: grain particle size; wholegrain flour; stone-milled flour; stoneground flour; glycaemia; acute blood glucose; whole grain; digestion; metabolism; insulin; 0908 Food Sciences; 1111 Nutrition and Dietetics